Development of pico-satellite : MEMS based ADCS sensors - Rahul Agrawal (2010)
Nanyang Technological University is aiming to design, develop and launch the first pico-satellite from Singapore. A pico-satellite, like any regular satellite, has several sub-systems that work together to constitute a single autonomous unit. These include power generation and supply, communications, on-board computer, attitude determination and control, mechanical structure etc.